1997
DOI: 10.1136/bmj.314.7089.1252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a decision support system for initiation and control of oral anticoagulation in a randomised trial

Abstract: Objectives: To determine whether a computerised decision support system for initiation and control of oral anticoagulant treatment improves quality of anticoagulant control achieved by trainee doctors. Design: Randomised controlled trial. Setting: District general hospital in North London. Subjects: 148 inpatients requiring start of warfarin treatment. Interventions: Management by trainee doctors (to achieve therapeutic range of international normalised ratio of 2 to 3) with indirect assistance from computeris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 19 publications
1
48
1
1
Order By: Relevance
“…46,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] These dosing adjuncts have been studied at the initiation of therapy (no prior VKA doses) and during the maintenance phase of therapy and were compared with dose deci sions made without the use of decision support (manual dosing). Both nomogram/computer-assisted and manual dosing were performed by experienced anticoagulation providers in some studies 78,86,87,90,91 and by providers without specialized training (eg, trainee physicians, house staff, regular physician, nurses) in others.…”
Section: Dosing Decision Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…46,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] These dosing adjuncts have been studied at the initiation of therapy (no prior VKA doses) and during the maintenance phase of therapy and were compared with dose deci sions made without the use of decision support (manual dosing). Both nomogram/computer-assisted and manual dosing were performed by experienced anticoagulation providers in some studies 78,86,87,90,91 and by providers without specialized training (eg, trainee physicians, house staff, regular physician, nurses) in others.…”
Section: Dosing Decision Supportmentioning
confidence: 99%
“…Both nomogram/computer-assisted and manual dosing were performed by experienced anticoagulation providers in some studies 78,86,87,90,91 and by providers without specialized training (eg, trainee physicians, house staff, regular physician, nurses) in others. 46,[79][80][81][82][83][84][85]88,89,[92][93][94][95] Decision support-guided dosing (paper nomograms or computer programs) performed no better than manual dosing during initiation of VKA therapy in pooled analyses of available RCTs ( Table 7 , Table S7). Pooled analyses of RCTs evaluating decision supportguided dosing during maintenance therapy (all were computer-assisted dosing programs) revealed a mean TTR improvement of 4.5% (95% CI, 2.4%-6.7%) compared with no decision support.…”
Section: Dosing Decision Supportmentioning
confidence: 99%
“…A systematic review of computerised drug dosing systems included five RCTs dealing with outpatient maintenance anticoagulation treatment, 32 of which one trial provided evidence that quality of initiation and control of warfarin treatment was improved by CDSS in comparison with usual care. 33 From this it can be concluded that until now there is no strong evidence of the effectiveness of measurement feedback systems, computerised drug dosing systems, or computerised guideline implementation systems in several chronic conditions in primary care. However, there is still a strong argument for the adoption of a measurement feedback system, or some other form of CDSS, in RA.…”
Section: Discussionmentioning
confidence: 98%
“…He developed an algorithm for warfarin dosing which was evaluated in a randomised controlled trial at the Whittington Hospital [18,19]. It was found that using the decision support tool the median time to achieve a stable dose was significantly lower, and both inpatients and outpatients spent longer within the therapeutic range than did patients dosed by unassisted trainee doctors.…”
Section: Methodsmentioning
confidence: 99%